Middle/Upper Paleolithic interface in Vindija Cave (Croatia): New results and interpretations - Karavanić, Ivor (Array, 2009)
Vindija cave in Croatia is a well-known site because of its association with fossil hominids and Middle and Upper Paleolithic stone industries. Several publications have discussed Neanderthal remains found alongside a Mosterian industry in level G3 and Upper Paleolithic bone points in level G1.This paper present recent results of faunal and lithic analysis from the G1 transitional level of the site, as well as a revision of the bone tools. Taphonomy of large mammals and hominid bones was examined. Although no human remains were found within the faunal assemblage, the results of this analysis are an important addition to understanding site formation processes, as well as Neanderthal behavior during the so-called transitional period. Based on the taphonomy of faunal and human remains from Vindija cave Level G1, we can strongly suggest that the Neanderthal were active predators. Human occupations were short and alternating with carnivore occupations.